An Analysis of the Implementation of Cloud-Based Accounting Software to Improve the Efficiency and Effectiveness of Financial Record-Keeping at CV Alfadh Parfum in Medan - Uci Kirani Rambe; Yenni Samri Juliati Nasution; Zuhrinal M Nawawi (FEBI IAIN Langsa, 2026)
The development of cloud-based accounting information systems has encouraged companies to undergo digital transformation in financial management. Previous research generally indicates that cloud-based accounting systems can improve operational efficiency and the quality of financial reporting. However, research that simultaneously measures improvements in efficiency and effectiveness and explains the underlying mechanisms of accounting information systems driving these improvements in small and medium-sized enterprises remains limited. This study aims to analyze the implementation of cloud-based accounting software in improving the efficiency and effectiveness of financial record-keeping at CV Alfadh Parfum. The research method used is a qualitative approach supported by quantitative analysis. The study was conducted at CV Alfadh Parfum in Medan, involving 10 informants consisting of the owner, an administrator, and employees who use the accounting system. Data were collected through interviews, observations, and documentation, then analyzed using the stages of data reduction, data presentation, and drawing conclusions, as well as quantitative analysis based on recording time and error rates before and after software implementation. The research findings show that the implementation of cloud-based accounting software (XAI) can improve the efficiency of financial record-keeping by 66.05%, as evidenced by a reduction in transaction recording time from 5 minutes to 2 minutes per transaction—equivalent to a time savings of 75 hours per month. In addition, the effectiveness of financial record-keeping also increased by 75%, as evidenced by a reduction in the error rate from 4 instances to 1 instance per day. These improvements in efficiency and effectiveness are supported by XAI’s system features, such as data validation through error alerts, transaction restrictions in case of discrepancies, transaction history, and real-time, transparent, and reliable reporting. Thus, the implementation of cloud-based accounting software not only improves operational efficiency but also enhances the accuracy, transparency, and quality of financial information to support decision-making.